Model Pembelajaran Discovery Learning Dan Media Film Pendek Pada Masa Pandemi Covid-19 - Siti Rejeki (LPMP Provinsi DKI Jakarta, 2021)
The purpose of the study was to improve student achievement and motivation to learn English in carrying out learning from home through discovery learning models and short film media. Classroom action research is the method used. Class X SMA Negeri 53 Jakarta, totalling 35 students as research subjects. Questionnaires, observations, and assignments as research instruments as well as quantitative and qualitative descriptive as data analysis techniques. The results of the study concluded that the students' motivation in improving achievement during learning from home was proven by the appearance of a short recount text film about the biography of Indonesian heroes in the first cycle, the lowest score was 70 and in cycle 2 the score was 50, from 35 students in two cycles the highest score was 94. This model can encourage students to be more active in learning